2011
DOI: 10.3109/10929088.2011.605173
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and accuracy of a novel rapid prototyping drill template for cervical pedicle screw placement

Abstract: This study demonstrates a patient-specific template technique that is easy to use, can simplify the surgical act, and generates highly accurate cervical pedicle screw placement. The advantages of this technology over traditional techniques are that it enables planning of the screw trajectory to be completed prior to surgery, and that the screw can be sized to fit the patient's anatomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
78
0
8

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(88 citation statements)
references
References 32 publications
2
78
0
8
Order By: Relevance
“…The concept of personalized image-based 3D templates was first described by Berry et al 4 Owen et al and Ryken and colleagues followed the concept with their cadaveric studies, 25,29,30 and then Lu and colleagues [16][17][18] and Kawaguchi et al 12 applied the templates for clinical use as drill guide templates. However, these templates were only used as a drilling guide.…”
Section: Discussionmentioning
confidence: 99%
“…The concept of personalized image-based 3D templates was first described by Berry et al 4 Owen et al and Ryken and colleagues followed the concept with their cadaveric studies, 25,29,30 and then Lu and colleagues [16][17][18] and Kawaguchi et al 12 applied the templates for clinical use as drill guide templates. However, these templates were only used as a drilling guide.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies demonstrated that the guides help to lower operation time, with Deng et al (37) suggesting this may decrease complications related to operative time (e.g., infection) (30,35,37,43). Other benefits include decreased intra-operative radiation, simplicity of use, elimination of procedural subjectivity, enhanced pre-operative planning and moderate cost in comparison with other techniques (30,(32)(33)(34)(35)(36)(37)(38)42,43).…”
Section: Surgical Guidesmentioning
confidence: 99%
“…In the cervical spine, asymmetry, vast inter-patient differences such as anomalous vertebral artery course, and the sensitive nature of surrounding tissues make procedural success more difficult to achieve, and hence able to benefit from individualised guides (30,31,33,34,37,38,40,43,56). Otsuki et al (41) demonstrated that 3DP guides provide an extra benefit in revision surgery, where screw insertion is more difficult due to morphology changes caused by the first operation.…”
Section: Surgical Guidesmentioning
confidence: 99%
See 2 more Smart Citations